Human Capital, Training Pathways and Educational and Professional Guidance in China - Doncel Abad, David (Sinología hispánica. China Studies Review, 2019)
One of the Government's priorities is to swap from an industrial economy and low salaries to one of Services and high salaries. For this, the government needs to increase the quality of Human Capital, understood as the increase in the average educational level of the population. An educational measure to achieve this goal is to enhance educational and vocational guidance. Orientation is conceived as a measure designed to optimize the adjustment between the education system and labor market. Although it is a measure present in the Chinese educational system before, it is not until 2012, when the government is committed to a model of Educational and Professional Guidance focused on the development of the individual's career. The objective of this paper is to analyze how educational transitions are from one educational stage to another, and from one educational level to another, to know the problems and factors associated with dropped from school. Once detected the different types of transition in the Chinese education system. We contrast it with the theoretical model of educational and professional guidance focused on the development of the individual's vocational career. At the methodological level, a review of the research and of the databases to be used is carried out. Finally, the results show how different itinerary models that Chinese students take according to their socio-educational profile do not fit with the theoretical model of Career Education.